2003
DOI: 10.1182/blood-2002-12-3837
|View full text |Cite
|
Sign up to set email alerts
|

Age-adjusted International Prognostic Index predicts autologous stem cell transplantation outcome for patients with relapsed or primary refractory diffuse large B-cell lymphoma

Abstract: Second-line chemotherapy followed by high-dose therapy (HDT) with autologous stem cell transplantation (ASCT) cures less than half of the patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL). Prognostic models capable of predicting outcome are essential. In 3 sequential clinical trials, conducted from January 1993 to August 2000, we treated 150 patients with relapsed or primary refractory DLBCL with ifosfamide, carboplatin, and etoposide (ICE) chemotherapy followed by HDT/ASCT for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
159
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(177 citation statements)
references
References 28 publications
(33 reference statements)
11
159
2
5
Order By: Relevance
“…The most significant adverse prognostic factors for response in both the whole series and the R+ group were the presence of bulky disease, primary refractory disease, an aaIPI higher than 1 at the time of R-ESHAP, as well as the administration of fewer than three cycles of R-ESHAP. Moreover, the presence of primary refractory disease and high-risk aaIPI at the time of R-ESHAP were also independent adverse prognostic factors for survival, in accordance with reports from other authors, 9,13,14,[23][24][25][26] but in contrast to the data published by Kewalramani et al, 13 who observed that the addition of rituximab to the ICE regimen seemed to overcome the adverse effects of an unfavorable IPI score. The dismal outcome of patients with primary refractory disease or with an unfavorable aaIPI at the time of relapse underlines the need for the evaluation of alternative treatments.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 57%
“…The most significant adverse prognostic factors for response in both the whole series and the R+ group were the presence of bulky disease, primary refractory disease, an aaIPI higher than 1 at the time of R-ESHAP, as well as the administration of fewer than three cycles of R-ESHAP. Moreover, the presence of primary refractory disease and high-risk aaIPI at the time of R-ESHAP were also independent adverse prognostic factors for survival, in accordance with reports from other authors, 9,13,14,[23][24][25][26] but in contrast to the data published by Kewalramani et al, 13 who observed that the addition of rituximab to the ICE regimen seemed to overcome the adverse effects of an unfavorable IPI score. The dismal outcome of patients with primary refractory disease or with an unfavorable aaIPI at the time of relapse underlines the need for the evaluation of alternative treatments.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 57%
“…An adaptation of the IPI, the age-adjusted IPI (aa-IPI, excludes age and extent of extra nodal disease) has been proposed as a better prognostic system in patients undergoing transplantation, reflecting the uniformly young population included in early series. Although aa-IPI at relapse did not predict the outcome of patients undergoing transplantation in the Parma trial, 15 this finding conflicts with subsequent series where IPI-R 16,17 or aa-IPI 18,19 were able to predict survival after transplantation. These series, although very informative, included multiple histologies of lymphoma, broad variety of conditioning regimens (some using TBI), heterogeneous source of stem cells and often restricted inclusion to younger patients.…”
Section: Transplantation; Beam Regimencontrasting
confidence: 55%
“…[6][7][8] Recently, the influence of comorbidity on outcome after autologous transplantation has also been reported by others. [13][14][15] However, none of these studies have compared comorbidity directly with sAAIPI scores or analyzed its predictive value for eligibility for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The sAAIPI has extensively proved its value in predicting response to reinduction therapy and final outcome in patients with relapsed aggressive NHL. [7][8][9] In our cohort, high-risk sAAIPI was highly predictive for both not receiving auto-SCT and survival. Probably because of the fact that only 5 out of 22 patients with sAAIPI scores of 3 ultimately received transplantation, the sAAIPI was no longer predictive for survival among the transplanted patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation